1997
DOI: 10.1042/bj3220393
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the rat cardiac troponin I gene by the transcription factor GATA-4

Abstract: Troponin I is a thin-filament contractile protein expressed in striated muscle. There are three known troponin I genes which are expressed in a muscle-fibre-type-specific manner in mature animals. Although the slow skeletal troponin I isoform is expressed in fetal and neonatal heart, the cardiac isoform is restricted in its expression to the myocardium at all developmental stages. To study the regulation of this cardiac-specific and developmentally regulated gene in vitro, the rat cardiac troponin I gene was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 61 publications
6
51
0
3
Order By: Relevance
“…When comparing the genomic regions upstream and downstream to the promoter of insect TnI genes, there is a striking conservation of the type and array of putative transcription factor binding sites ( Figure 6). For the rat slow, quail fast, and rat cardiac TnI genes, there are expression studies similar to those reported here, albeit in transfected cells (Yutzey et al, 1989;Banerjee-Basu and Buonanno, 1993;Nakayama et al, 1996;Murphy et al, 1997). With the exception of the rat cardiac gene, two regulatory regions upstream and downstream of the transcription initiation site have been documented.…”
Section: Conservation Of the Tni Regulatory Arraysupporting
confidence: 57%
“…When comparing the genomic regions upstream and downstream to the promoter of insect TnI genes, there is a striking conservation of the type and array of putative transcription factor binding sites ( Figure 6). For the rat slow, quail fast, and rat cardiac TnI genes, there are expression studies similar to those reported here, albeit in transfected cells (Yutzey et al, 1989;Banerjee-Basu and Buonanno, 1993;Nakayama et al, 1996;Murphy et al, 1997). With the exception of the rat cardiac gene, two regulatory regions upstream and downstream of the transcription initiation site have been documented.…”
Section: Conservation Of the Tni Regulatory Arraysupporting
confidence: 57%
“…Of interest, sitedirected mutagenesis of either element eliminated the expression of this promoter. Since a mutation of the GATA element in the rat (Murphy et al, 1997) and human (Bhavsar et al, 2000) TnIc promoters was shown to reduce promoter activity by 94% and 80%, respectively, the observation that GATA transcription factors are involved in initiating/regulating TnIc expression in this amphibian were not unexpected. However, that mutation of a CArG-box motif (the binding site for a serum response factor) in the amphibian TnIc promoter also eliminates its expression was novel.…”
Section: Discussionmentioning
confidence: 95%
“…Because the only vertebrate TnIc gene sequences reported to date are from mammals (Ausoni et al, 1994;Bhavsar et al, 1996;Murphy et al, 1997), we compared the size and organization of this amphibian gene with its mammalian homologues and found that it is 6 -10 times larger than any of its mammalian counterparts. The R. catesbeiana TnIc gene contains nine introns, whereas only seven introns have been identified in the mammalian TnIc genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations